Sistem Rumah, Amalan Kepengetuaan dan Kecemerlangan Pendidikan di Sekolah Alam Shah, Kuala Lumpur, 1979-1993 - Haron, Hassan (2009)
The study was to explore and establish the extent to which the House System was the phenomenon that contributed to the achievement of educational excellence in four aspects: academic, co-curricular activities, discipline and student leadership in the chosen school. It also tried to establish how far the principals' practices were the phenomena that fluctuated the achievement of educational excellence in those aspects. The study has developed a basis for a pattern theory from the patterns of principals' practices in implementing the House System. The qualitative and quantitative methods were used to collect data so as to establish the relationships among the research factors: the House System as the contributing factor, educational excellence as the resulting factor and the principal practice as the causing factor. The research was historical, covering a 15-year period (1979-1993) and based on a case study of the educational programme being implemented in Sekolah Alam Shah. The findings show that there are strong relationships between the House System and the principals' practices and the educational excellence. The study also reveals that the patterns of practices of the five principals in implementing the programme had contributed to the performances of the four aspects of educational excellence. Those patterns were grouped into three categories; the consistent practice that raised excellent performances in the aspects; the less consistent practice which fluctuated the achievement level in the upper rung; while the inconsistent practice fluctuated achievement in the lower rung. From the established patterns of principals' practices, the pattern theory is developed inductively, that "the consistent pattern of principal practices, raised the educational achievement to the excellent level".This pattern theory based on the established patterns of principals' practices could be called the theory of the practice of generator principal because the pattern of consistent practices generated the energy of motivation and commitment among the staff and students to realise the objective of the House System. This theory met the five features of pattern theory by Lincoln and Guba (1985) and Neuman (1991). The findings are significant that they provide major implications to the planning and management of national education system. The House System as an educational programme could generate educational excellence in academic, co-curricular activities, discipline and student leadership.